Website-Based Room Reservation System in UNESA Library - Kurnia, Asna; Maslihah, Maslihah (Melek IT : Information Technology Journal, 2025)
The Surabaya State University Library Unit (UPT) provides several rooms for both academic and non-academic activities. The existing borrowing system, which is still conducted through Google Forms, presents challenges such as scheduling conflicts, slow administrative processes, and the risk of fictitious reservations. This research aims to develop a website-based room borrowing information system that can provide real-time availability information, validate borrowing data, and provide organized reports. The system was developed using the waterfall method, with stages of analysis, design, implementation, and testing. The results show that the system is capable of displaying room schedules, managing reservation data, and generating reports in PDF format. Blackbox testing demonstrated that all functions function as required. With this system, the room borrowing process at the UNESA Library Unit has become more effective and efficient, and facilitates both administrators and users in managing activities.